Agenda clic to dial sobre plataforma lampa - Naranjo Paredes, Ronald (2010)
The current Project is about the development of a phonebook ready to clic to dial over a LAMPA platform, which means developed over a Apache web site , with database storage for data in MySQL and PHP language for connect to Asterisk PBX Telephony. Whole the project is manufactured under linux platform. The main function of our project is make calls with one clic, which is why the web site is designed with several search fields for making the users easiest to locate phone contacts. The project is based in one important part which is the Open Source PBX software Asterisk that let us make calls over the most standards protocol to communicate over the internet, they are SIP and IAX. The web site was developed to be launched on Internet Explorer, Mozilla firefox, Google Chrome because it doesn´t need any additional plug-in